THU0209 Follow up observations of the patients with rheumatoid arthritis (ra) and reactive amyloidosis. (1st June 2001) - Stanislawska-Biernat, E; Filipowicz-Sosnowska, A; Wagner, T; Prohorec-Sobieszek, M
Abstract : Background: Secondary amyloidosis is a serious complication of rheumatoid arthritis and may result in significant morbidity and early death. The knowledge on standard and effective management of patients with secondary amyloidosis is limited. Objectives: The objective of the study is follow up observation of RA patients with established reactive amyloidosis concerning the clinical aspects of the disease, acute phase reactants and the response to cytostatic treatment. Methods: 43 patients with rheumatoid arthritis and histologically confirmed secondary amyloidosis were followed for 3 to 6 (mean 4, 6) years. The patients were treated with cyclophosphamide or methotrexate combined with small doses of prednizone. Clinical symptoms, laboratory tests and general outcome were analysed after 3 to 6 years of development of amyloidosis. Results: The time from the diagnosis of RA to the development of amyloidosis was 4 to 16 years, mean 8, 7 years. In all patients advanced radiological changes were observed (radiological Steinbrocker stage III or IV). The most common symptoms of amyloidosis were: proteinuria-27(62, 8%), nephrotic syndrom -12(27, 9%), diarrhoea-4(9, 3%). In most of the patients the course of RA was very severe since the onset and high activity parameters were observed despite treatment. Amyloidosis was histologically confirmed by subcutaneous fat tissue biopsy in 38(88, 4%) cases. In 8 patients amyloid deposits were found in other organs (kidney, stomach, salivary gland). After the treatment with cyclophosphamide or methotrexate we observed decrease of some activity parameters (ESR, CRP) and decrease of proteinuria level. The treatment was well tolerated and we didn?t observe serious side effects. In the observed group 7(16, 3%) patients died after 3 to 6 years of the diagnosis of amyloidosis. The most common cause of death were uremia (4/7) and infections (2/7). Conclusion: Aggressive treatment with cytostatics influences the survival of patients with reactive amyloidosis in RA. The time of survival in 83, 7% of the observed patients was longer than 4, 6 years. The outcome of patients with RA and reactive amyloidosis is better when the diagnosis of amyloidosis is confirmed in the early stage of the disease.